2001
DOI: 10.5172/conu.10.1-2.30
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a problem based learning course: An action research study

Abstract: Problem based learning (PBL) has been widely used in the United States, United Kingdom and Australasia in undergraduate nursing education to develop critical thinking and problem solving skills. PBL has been used since 1996 in a Bachelor of Nursing course at a New Zealand tertiary institution, and several modifications have been made to foster effective learning. The 'pure' PBL process has been adapted to move students gradually from teacher direction to taking responsibility for their learning. This has provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Current findings consistent with the previous findings (Walker et al, 2001;Wood, 2006;Yuan et al, 2011a) suggested that the PBL process has been adapted to move students gradually from teacher direction to taking responsibility for their learning. This has provided the opportunity for students to develop critical thinking, problem solving, information retrieval and evaluation skills, and group process skills over an 18-week period.…”
Section: Discussionsupporting
confidence: 90%
“…Current findings consistent with the previous findings (Walker et al, 2001;Wood, 2006;Yuan et al, 2011a) suggested that the PBL process has been adapted to move students gradually from teacher direction to taking responsibility for their learning. This has provided the opportunity for students to develop critical thinking, problem solving, information retrieval and evaluation skills, and group process skills over an 18-week period.…”
Section: Discussionsupporting
confidence: 90%
“…Over the past decades, much effort has been invested in the implementation of PBL at both programme and subject levels in different parts of the world. Curricula have been restructured, PBL learning packages have been prepared, teaching-learning activities have been reorganized, and new assessment methods have been introduced (Baker 2000, Houlden et al 2001, Johnston & Tinning 2001, Morales-Mann & Kaitell 2001, Walker et al 2001. Nonetheless, PBL implementation has revealed a number of longstanding problems that have roots not only in the educational system but also within the clinical context.…”
Section: Introductionmentioning
confidence: 99%